1994
DOI: 10.1159/000284844
|View full text |Cite
|
Sign up to set email alerts
|

Testing the Comparability of Psychiatric Diagnoses in ICD-10 and DSM-III-R

Abstract: The compatibility of the classification systems ICD-10 and DSM-III-R was investigated in a sample of 100 psychiatric inpatients with severe affective and psychotic disorders. Four independent raters assessed diagnoses by means of checklists from psychopathological descriptions of case records. Congruence between ICD-10 and DSM-III-R was good for depressive disorders with agreement rates above 80% and fair for bipolar disorders with rates above 60%. Less consistent findings were obtained for schizophrenia with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
11
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 13 publications
(22 reference statements)
3
11
0
1
Order By: Relevance
“…Three studies reported interrater reliability values within the range of the present study [17,23,24] . However, other studies found considerably higher values [2,13,15,21,[25][26][27][28][29][30] .…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…Three studies reported interrater reliability values within the range of the present study [17,23,24] . However, other studies found considerably higher values [2,13,15,21,[25][26][27][28][29][30] .…”
Section: Discussionsupporting
confidence: 68%
“…The higher frequency of diagnosis of schizophrenia according to ICD-10 than DSM-IV or DSM-III-R has also been reported in two additional studies [17,18] , although other studies failed to detect this difference [2,13,[19][20][21] . Indeed, ICD-10 criteria for schizophrenia seem to be less restrictive.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Furthermore, the reliability of using diagnosis codes from medical claims to identify schizophrenia and related disorders may be questionable. 28,29 Though not specifically recommended in the product labeling or in current treatment guidelines for schizophrenia 30 or bipolar disorder, 31 the use of polytherapy with multiple atypical antipsychotic medications has been identified as an increasingly common practice. 15,17,32,33 Thus, we were not surprised to find that many patients were receiving multiple antipsychotic medications concomitantly.…”
Section: Ss Discussionmentioning
confidence: 99%